Prenatal diagnosis and eugenic abortion in Spanish Law 2/2010 - Germán Zurriaráin, Roberto (Polish Journal of Public Health, 2013)
Introduction. Since abortion was legalized in Spain in 1985, and official prenatal diagnosis programs implemented, eugenic abortion figures have raised yearly. The increase in use of prenatal diagnosis techniques has led, in turn, to the rise of a new form of discrimination, which is based on age and health conditions, against a vulnerable human group: disabled unborn.Aim. To promote a new judicial framework for establishing a true regime for protecting human life right from the outset.Material and methods. To achieve these goals a thorough review of the literature with regard to eugenic abortion and the Spanish Law has been undertaken.Results. The Spanish Law 2/2010 allows one to aborta fetus that’s physical or psychic differences were compatible with life and did not pose any danger to the mother, which would result in a clear case of legal discrimination, based on incapacity or a form of functional diversity or difference. The fetuses with disabilities (up to 22-week of pregnancy), in Law 2/2010, are not equal to others, since the disabled “nasciturus” receives less protection than the rest.Discussion. A deep ethical debate regarding prenatal diagnosis is necessary. Nonetheless, the current socio-political framework in Spain makes the therapeutic use of prenatal diagnosis inseparable from its eugenic use, which, in turn, determines the bio sanitary framework when promoting abortion of disabled human beings and after a positive prenatal diagnosis.Conclusions. The Spanish Law 2/2010 presumes the right to abortion until the 14th week of pregnancy because the “nasciturus” depends exclusively on the mother’s will as if it were part of her. The legalization of eugenic abortion represents an open violation of the constitutional principle of non-discrimination and of equal access to health care independent of disability.